Magnetic susceptibility for characterizing areas with different potentials for sugarcane production - Siqueira, Diego Silva [UNESP]; Júnior, José Marques [UNESP]; Teixeira, Daniel De Bortoli [UNESP]; Matias, Sammy Sidney Rocha; Camargo, Livia Arantes [UNESP]; Pereira, Gener Tadeu [UNESP] (FapUNIFESP (SciELO), 2016)
The objective of this work was to evaluate the use of magnetic susceptibility for characterizing the spatial variability of soil attributes and identifying areas with different potentials for sugarcane (Saccharum spp.) production. Samples were collected at 110 points (1 per 7 ha) in the layers of 0.00-0.20 and 0.20-0.40 m, to determine the magnetic susceptibility and physical and chemical attributes of the soil. Fiber content, sucrose polarization (POL), and sugarcane yield were determined in 33 points. The spatial variability model for magnetic susceptibility was 63 and 22% more accurate in delimiting soil potential for sugarcane production than soil physical and chemical attributes at the 0.0-0.2 and 0.2-0.4-m layers, respectively. The spatial variability map for magnetic susceptibility was strongly correlated with clay (0.83 and 0.89, respectively, for the layers) and sand contents (-0.84 and-0.88); moderately correlated with organic matter (-0.25 and-0.35), sum of bases (-0.46 and 0.37), cation exchange capacity (0.22 and 0.47), pH (-0.52 and 0.13), and POL (0.43 and 0.53); and weakly correlated with sugarcane yield (0.26 and 0.23). Magnetic susceptibility can be used to characterize the spatial variability of soil attributes and to identify areas with different potentials for sugarcane production.
Keywords: Detailed mapping; Geostatistics; Indirect quantification; Pedometrics; Scaled semivariogram; Spatial correlation